SARS-CoV-2 Infection and Sequelae in Febrile Patients in Six Hospitals along the Thai-Lao and Thai-Myanmar Borders, 2022-2023 - Dr Saithip Bhengsri; Dr. Emily Bloss; Dr. Pongpun Sawatwong; Dr. Nuttagarn Chuenchom; Dr. Tanaphat Lertwitayakumjorn; Dr. Barameht Piralam; Mr. Samkan Chaoprasert; Mr. Tuwan Simmali; Ms. Pornpan Bungkanjana; Dr. James D Heffelfinger; Dr. Anupong Sujariyakul (International Journal of Infectious Diseases)
Background: Reports of persistent symptoms after COVID-19 infection have raised concern about post-COVID conditions (PCC). We describe patient characteristics and risk factors for COVID-19 infection and PCC at six months after enrollment in febrile patients presenting to six hospitals in Nakhon Phanom and Tak provinces, along the Thai-Lao and Thai-Myanmar borders, respectively. Methods: During June 2022-May 2023, we enrolled patients aged >2 years presenting to outpatient departments/emergency rooms with temperature ≥37.5°C or history of fever ≤14 days. Saliva, nasal and nasopharyngeal/oropharyngeal swabs were tested for SARS-CoV-2 using real-time RT-PCR. Interviews and medical record reviews were conducted. Differences between COVID-19 cases (patients with RT-PCR positive for SARS-CoV-2) and non-cases were measured using Chi-square test. Multivariate analysis assessed factors associated with COVID-19; adjusted odds ratios (aOR) and 95% confidence intervals (CI) were calculated. Follow-up of cases has occurred every three months following enrollment to assess PCC (defined as any persistent symptoms at each follow-up period) and degree of depression using the Patient Health Questionnaire (PHQ-9), compared to baseline at enrollment. Results: COVID-19 was detected in 1,694/3,031 (56%) persons, including 1,173/1,802 (65%) from Nakhon Phanom and 521/1,229 (42%) from Tak (p<0.001). Compared to non-cases, cases were more likely to be older (median 38 [interquartile range 28-54] vs. 28 [IQR 13-49] years, p<0.001) and female (63% vs. 53%, p<0.001). Cases were more likely to report contact with other COVID-19 cases (aOR 10.0; 95%CI 7.8-12.0), history of travel (aOR 2.8; 95%CI 2.0-4.1), visiting crowded places (aOR 1.3; 95%CI 1.1-1.6), current alcohol consumption (aOR 1.9; 95%CI 1.3-2.8) and obesity (aOR1.5; 95%CI 1.3-1.8).Of 1,694 cases, 842 (50%) agreed to be monitored for PCC, 420 (50%) completed six months of follow-up. Half (210/420) of these cases reported persistent symptoms at the 6-month follow-up visit; fatigue (n=80, 19%), muscle pain (n=79, 19%), forgetfulness (n=76, 18%), insomnia (n=74, 18%) and shortness of breath (n=38, 9.0%) were the most common symptoms described by cases. A similar pattern of symptoms was observed among 442 participants at the 3-month follow-up visit. The proportion of cases with moderate to severe depression decreased from 4.3% (19/442) at baseline to 1.9% (8/420) at six months (p=0.08). A greater proportion of females than males reported moderate to severe depression at baseline (5.8% vs. 1.3%, p=0.03) and at 6-month follow-up (2.6% vs. 0.4%, p=0.04). Discussion: SARS-CoV-2 was detected in more than half of febrile patients visiting hospitals in two border provinces of Thailand. Understanding the risk factors may inform prevention strategies for SARS-CoV-2 infections. PCC was found in half of the COVID-19 patients six months after COVID-19 diagnosis. Conclusion: Public health authorities and health care providers should work with communities to reduce risks for infection and monitor patients for PCC and mental health status after infection.